The Holocaust in Thessaloniki : reactions to the anti-Jewish persecution, 1942-1943 - Saltiel, Leon (Routledge Jewish studies series, 2020)
"The book narrates the last days of the once prominent Jewish community of Thessaloniki which, in 1943, was transported to the Nazi death camp of Auschwitz. Focusing on the Holocaust of the Jews of Thessaloniki, this book maps the reactions of the authorities, the Church and the civil society as events unfolded. In so doing, it seeks to answer the questions, did the Christian society of their hometown stand up to their defence and did they try to undermine or object to the Nazi orders? Utilizing new sources and interpretation schemes, this book will be a great contribution to the local efforts underway, seeking to reconcile Thessaloniki with its Jewish past and honour the victims of the Holocaust. The first study to examine why 95 per cent of the Jews of Thessaloniki perished, one of the highest percentages in Europe, this book will appeal to students and scholars of the Holocaust, European History and Jewish Studies"--